Understanding dynamics of gluten harvest in augmenting bread quality in high yielding Indian wheats - Mohan, D.; Gupta, R.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Ten years data of bread wheat entries evaluated under different environments in India was utilized to understand the factors influencing wet gluten content in high-yield genotypes. Study based on 503 entries revealed that besides genetic factors; agro-climatic variations, production conditions, protein-gluten ratio, water soaking capacity of gluten and HMWGS at Glu D1 also influenced harvest of wet gluten. Regional specificity was noticed in proteingluten ratio, which was low in cooler climate and high under hot and dry conditions. Protein-gluten ratio and water retention emerged as characteristic features of a zone and were hardly influenced by varying crop duration of genotypes tested within the zone. While collating gluten characteristics with bread making quality, it was observed that high wet gluten, derived from better gluten proteingluten ratio and water soaking capacity, made a crucial difference.